The mitochondrial landscape of African Americans: An examination of more than 2500 control region haplotypes from 22 U.S. locations. (May 2016) - Scheible, M.; Just, R.; Sturk-Andreaggi, K.; Saunier, J.; Parson, W.; Parsons, T.; Coble, M.; Irwin, J.
Highlights: 2563 African American mtDNA control regions were Sanger-sequenced following forensic guidelines. 20 of 22 population samples were found to be statistically indistinguishable. Population data are made available via EMPOP (empop.org ) and GenBank. Abstract: The mitochondrial DNA (mtDNA) control region (16024-576) was Sanger-sequenced for a total of 2563 self-identified African Americans, using automated processing techniques and data review standards exceeding guidelines for forensic applications. Genetic diversity ranged from 0.9952 to 0.9998 in 22 population samples from 20 different states. Haplogroups of African ancestry, found in 82.48% of individuals overall, were most concentrated in the Southeast U.S. and decreased to the north and west. West African and West Central African haplotypes were well-represented in the population samples, especially in the southern U.S. states, while East African haplogroups were observed in low-frequency clusters in a handful of locations across the country. East Asian, Native American, and West Eurasian admixture was present in 3.16%, 2.93%, and 11.43% of samples, respectively. While some geographic substructure was detected across the population samples as clines in admixture frequencies, 20 of the 22 population samples were found to be statistically indistinguishable by pairwise comparisons and AMOVA calculations. Datasets from Hawaii and Idaho, however, were clear outliers. Overall, these more than 2500 control region sequences represent the most comprehensive regional sampling of African American mtDNA diversity to date, and are suitable for use in a forensic mtDNA database. The population data are made available via EMPOP (www.empop.org ) and GenBank.